Effects of lubricant and autologous bone marrow stromal cell augmentation on immobilized flexor tendon repairs. Issue 1 (31st July 2015) - Zhao, Chunfeng; Ozasa, Yasuhiro; Shimura, Haruhiko; Reisdorf, Ramona L.; Thoreson, Andrew R.; Jay, Gregory; Moran, Steven L.; An, Kai‐Nan; Amadio, Peter C.
ABSTRACT: The purpose of the study was to test a novel treatment that carbodiimide‐derivatized‐hyaluronic acid‐lubricin (cd‐HA‐lubricin) combined cell‐based therapy in an immobilized flexor tendon repair in a canine model. Seventy‐eight flexor tendons from 39 dogs were transected. One tendon was treated with cd‐HA‐lubricin plus an interpositional graft of 8 × 10 5 BMSCs and GDF‐5. The other tendon was repaired without treatment. After 21 day of immobilization, 19 dogs were sacrificed; the remaining 20 dogs underwent a 21‐day rehabilitation protocol before euthanasia. The work of flexion, tendon gliding resistance, and adhesion score in treated tendons were significantly less than the untreated tendons ( p  < 0.05). The failure strength of the untreated tendons was higher than the treated tendons at 21 and 42 days ( p  < 0.05). However, there is no significant difference in stiffness between two groups at day 42. Histologic analysis of treated tendons showed a smooth surface and viable transplanted cells 42 days after the repair, whereas untreated tendons showed severe adhesion formation around the repair site. The combination of lubricant and cell treatment resulted in significantly improved digit function, reduced adhesion formation. This novel treatment can address the unmet needs of patients who are unable to commence an early mobilization protocol after flexor tendon repair. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:154–160, 2016.